Cues and clues predicting presence of symptoms of depression in stroke survivors. Issue 3 (19th September 2016) - Barra, Mathias; Evensen, Gina Sophie Hvidsten; Valeberg, Berit Taraldsen
Abstract : Aims and objectives: To investigate to what extent self‐reported cues about lack of treatment or concerns about inadequate health care from stroke survivors were associated with symptoms of depression. Background: Stroke survivors are prone to depression, and thus, any easily available cues which may inform healthcare workers about patients' mental well‐being are potentially important. This study investigates whether two such cues – Cue 1 the subjectively reported lack of access to rehabilitation, and more generally, Cue 2 an expressed concern that their healthcare needs may not be adequately met – may be clinically relevant to be on the outlook for. Design: A cross‐sectional survey of stroke survivors three months after discharge from a stroke unit. Methods: Analysis of data on stroke survivors collected at three months after discharge from a hospital's stroke unit, by means of a mailed questionnaire. Descriptive statistics for the sample population were computed, and a binary logistic model fitted to estimate the impact of subjectively perceived lack of rehabilitation and subjectively reported low confidence in the healthcare system on symptoms of depression as measured by the Hospital Anxiety and Depression Scale. Results: The percentage of patients reporting the presence of symptoms of depression three months postdischarge (22·6%) was consistent with the main body of literature on this subject. Both cues investigated had a significant ( p  < 0·05) and elevated odds ratio–Cue 1 odds ratio = 4·7 (1·3–18·4) and Cue 2 odds ratio = 2·8 (1·2–6·4), respectively – for showing symptoms of depression in our population. Conclusion: Healthcare workers who come in contact with stroke survivors who report having missed out on rehabilitation or express concern that their care needs may not be adequately met by their access to health care should ensure that the patients' mental well‐being is being duly monitored and should consider further investigation for depression. Relevance to clinical practice: Healthcare workers who come into contact with stroke survivors should pay attention to patients' remonstrance of access to rehabilitation, or concerns about adequacy of received care, as these might constitute cues for the presence of symptoms of depression.